2021
DOI: 10.3389/fimmu.2021.646450
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Glucocorticoid Administration and the Risk of Impaired Efficacy of Axicabtagene Ciloleucel Treatment: A Systematic Review

Abstract: BackgroundGlucocorticoid is one of the common and important strategies for the treatment of chimeric antigen receptor T (CAR-T) cell therapy-related toxicity. However, there has been a theoretical concern about whether glucocorticoids use can impact the expansion of CAR-T cells and thus impair its efficacy. Hence, we reviewed studies related to the Axicabtagene ciloleucel (Axi-cel), a first-class and widely used CAR-T cell product, to elucidate the association between glucocorticoids administration and efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
(70 reference statements)
1
15
0
Order By: Relevance
“…Dex is used to treat several different kinds of cancer, such as multiple myeloma and glioblastoma (45, 46), as well as to treat immune-related toxicities associated with CAR T cell therapy. While there is concern that dex may decrease the function and persistence of CAR T cells (18, 19), we found that dex enhanced the efficacy of CAR T cells in our model ( Figure 7, Figure S7 ). These results are supported by the recent clinical observation that CAR T cells had better expansion and persistence in patients who received dex compared patients who did not receive dex (20).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Dex is used to treat several different kinds of cancer, such as multiple myeloma and glioblastoma (45, 46), as well as to treat immune-related toxicities associated with CAR T cell therapy. While there is concern that dex may decrease the function and persistence of CAR T cells (18, 19), we found that dex enhanced the efficacy of CAR T cells in our model ( Figure 7, Figure S7 ). These results are supported by the recent clinical observation that CAR T cells had better expansion and persistence in patients who received dex compared patients who did not receive dex (20).…”
Section: Discussionmentioning
confidence: 66%
“…Binding of GCs to the glucocorticoid receptor (GR) causes GR dimerization and translocation to the nucleus, where GRs can modulate expression of genes that contain a glucocorticoid response element (GRE) (5)(6)(7)(8)(9), including those involved in T cell proliferation and survival. In general, GCs are not routinely given to patients receiving CAR T cells, except to treat severe neurotoxicity associated with CAR T cell therapy, due to the concern that GCs may dampen CAR T cell activity and persistence (18,19). However, recent evaluation of clinical data suggests that treatment with GCs, including the synthetic GC dexamethasone (dex), does not affect proliferation or persistence of CAR T cells (20).…”
Section: Introductionmentioning
confidence: 99%
“…Protected by copyright. http://jitc.bmj.com/ safety outcomes for a specific CAR-T cell therapy or a specific indication, [82][83][84][85][86][87][88][89] but the correlation between dose and related factors and response was not studied. To derive from the combined knowledge of all relevant clinical studies, all CAR-T cells therapies for hematological cancers were analyzed together for correlations and then analyzed separately based on target antigens as well as intracellular domains.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids are used for CRS resistant cases and for CAR-related neurological complications (32). Some reports indicate that corticosteroids can negatively affect CAR T-cell persistence and function (39,40), while other reports do not link steroids to poorer outcomes (41). Nonetheless, CAR T-cell therapies that do not induce deleterious, systemic inflammation may prove more efficacious than existing ones.…”
Section: Discussionmentioning
confidence: 99%